PENGARUH CITRA MERK DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS KONSUMEN (Studi Kasus Perilaku Konsumen Toko Roti Lyly Bakery) - Bhiaztika Ristyanadi; Yunni Rusmawati Dwi Jayanti (JPIM (Jurnal Penelitian Ilmu Manajemen), 2018)
Study was to (1) analyze the image of the brand Lyly Bakery, (2) analyze consumer satisfaction Lyly Bakery, (3) analyze consumer loyalty Lyly Bakery, and (4) analyze the influence of brand image and customer satisfaction to customer loyalty Lyly Bakery. Implementation of the assessment of these parameters is done by scoring method. This study in the form of questionnaires containing questions for the items given a response by the respondent researchers.The influence of brand image on customer loyalty to the product Lyly Bakery. The analysis technique used is to use multiple linear regression models. Constant values (a) obtained for 0046, which means if the brand image variable does not exist then it is assumed that consumer loyalty is formed by 0046. Brand image regression coefficient (b) of 0.379 indicates when there is an increase in the brand image will enhance customer loyalty Lyly Bakery. The coefficient of determination (adjusted R2) was obtained for 0447, which means contributions pangaruh brand image variable, is equal to 44.7% and the remaining 55.3% is explained by other factors outside the model. This means that the variable brand image can provide a major influence on changes in consumer loyalty Lyly Bakery. Keyword: brand image, customer satisfaction, customer loyalty